Changing regimes, debt structure and bank fragility in Mexico - Cermeño, Rodolfo; Hernández Trillo, Fausto; Villagómez Amezcua, Alejandro (Estudios Económicos de El Colegio de México, 2001)
This paper uses the switching probability regimes methodology to estimate the determinants of financial crisis, measured in changes in the stochastic regimes of interest and exchange rates. We use Mexico to perform the exercise. Results suggest that public debt structure is important in explaining the so-called tequila crisis. This result contrasts with the determinants identified by the existent literature. In addition, financial fragility measured as the ratio of M2 to reserves, was also important in explaining the regimes under study.